(untitled) (Third Sector Social Economic Review, 2018)
Participation Insurance, which dates back to Hamurabi laws in B.C. 1800, depends on contracts made with companies specialized in this field which aim to minimize/eliminate risks and form a type of assurance at the cost of a prepaid premium. Although insurance as a sector has developed as expected in the West since the beginning, it didn’t take much place in Muslim nations due to Islam’s orders and bans for a long time. Since Muslims needed to adopt a lifestyle required by Islam and also the insurance products to protect themselves from possible risks, alternative insurance studies regarding Muslim countries started in 1970’s and formed the Participation Insurance sector. Takaful is terminologicall defined as Participation Insurance in today’s world and is based on cooperation and sharing. Total income of Participation Insurance around the globe was estimated to be 14,9 billion in 2015 and grew 14%. Although this interest-free system is newly introduced and even younger than ten years in Turkey, the demand for it has been growing for 40 years in the Muslim world. This study aims to discuss the definition of insurance, its history, its types and its applications along with the importance of this financial system which started to develop in the last years in Turkey and its strengths and weaknesses, opportunities and threats with the help of a SWOT analysis.